Clinical profile of hypertensive patients presenting to the emergency department - Yerra Vinayak; Madhusudan Mukkara; A Krishna Simha Reddy; N Harini Devi; M R Kiran Kumar; Rani Jonnakuti (Journal of Clinical and Scientific Research, 2020)
Background: The clinical profile of patients with hypertension presenting to emergency is understudied and unknown in developing countries like India. Method: We prospectively studied the clinical profile, target organ damage, laboratory parameters and imaging parameters in 532 patients with hypertension (461 [86.7%] previously known hypertensives and 71 [13.3%] newly diagnosed hypertensives) presenting to the emergency department at our tertiary care teaching hospital. Results: Their mean age was 57 ± 13.2 years; 65.6% were males. Neurological deficits (n = 164; 30.8%) were the commonest presenting symptom followed by chest pain (n = 143; 26.9%) and dyspnoea (n = 109; 20.5%). Hyponatremia (n = 188; 35.3%) and hyperkalemia (n = 59; 11.1%). Cerebrovascular accidents were the commonest target organ damage. Higher blood pressure at presentation and at 8 hours were associated with fatal outcomes. Conclusion: Target organ damage was higher in known hypertensives with poor drug compliance and higher age groups particularly males. Cerebrovascular accidents were the commonest mode of presentation.